2018
DOI: 10.1021/acsaem.8b02007
|View full text |Cite
|
Sign up to set email alerts
|

Compact Lithium-Ion Battery Electrodes with Lightweight Reduced Graphene Oxide/Poly(Acrylic Acid) Current Collectors

Abstract: We report the fabrication and electrochemical performance of metal-foil free Li4Ti5O12 (LTO) and LiNi1/3Co1/3Mn1/3O2 (NCM) electrodes supported on conductive and porous reduced graphene oxide/poly­(acrylic acid) (rGO-PAA) aerogels. The highly porous rGO-PAA (∼6 mg cm–3) enables slurry infiltration of LTO and NCM to form composite electrodes with tunable mass loadings (∼3–30 mg cm–2), and the resultant composites can withstand 100-fold compression (from 3.2 mm to ∼30–130 μm) to achieve electrode densities of 2–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 38 publications
0
13
0
2
Order By: Relevance
“…A high-density energy storage system is highly in demand for electric vehicles and flexible energy systems requiring a portfolio of various distributed energy resources. Extensive research has been considerably expanded over the last few years to develop innovative green energy-storage devices such as batteries and supercapacitors to cope with highly intermittent demand on electric energy storage [ 1 , 2 , 3 , 4 , 5 ]. Most of the energy-storage devices are based on batteries, which still have low power density and safety issues [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A high-density energy storage system is highly in demand for electric vehicles and flexible energy systems requiring a portfolio of various distributed energy resources. Extensive research has been considerably expanded over the last few years to develop innovative green energy-storage devices such as batteries and supercapacitors to cope with highly intermittent demand on electric energy storage [ 1 , 2 , 3 , 4 , 5 ]. Most of the energy-storage devices are based on batteries, which still have low power density and safety issues [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical tests demonstrated a specific capacity of 176.6 mAh g −1 at a rate of 1C, a rate capability of 167 and 143 mAh g −1 at 3C and 10C, respectively, and a capacity retention of 95.4% after 100 cycles at 10C. Pender et al [370,371] reported the fabrication and electrochemical performance of metal-foil free Li 4 Ti 5 O 12 (LTO) and LiNi 1/3 Mn 1/3 Co 1/3 O 2 (NMC) electrodes supported on conductive and porous reduced graphene oxide/poly(acrylic acid) (rGO-PAA) aerogels. This 3D nanocomposite had a low density (~5 mg cm −3 ) and high porosity (99.6% void space) [370].…”
Section: Molybdenum-based Oxide Compositesmentioning
confidence: 97%
“…When applied as a free-standing, 3D current collector in LIBs, the highly porous rGO-PAA substrate increased the effective electrode−electrolyte contact area 2.5-fold (16 mg cm −2 loading) by increasing the electrode surface roughness and thus improving the lithiation/delithiation kinetics of a commercial LFP cathode [372]. The use of rGO-PAA instead of conventional metal-foil (CMF) showed a 25% increase in energy density over similar electrodes built with CMF current collector, i.e., high volumetric energy densities of 1723 Wh L −1 for NMC and 625 Wh L −1 for LTO [371].…”
Section: Molybdenum-based Oxide Compositesmentioning
confidence: 99%
“…Reproduced with permission from Kong et al (2018b). 2019), foam-like current collectors (Mukanova et al, 2017(Mukanova et al, , 2018Lu et al, 2019), porous reduced graphene oxide/poly(acrylic acid) (rGO-PAA) aerogels based current collectors (Pender et al, 2019). These approaches revolve around the idea of changing the planar architecture of conventional current collectors to confine dendritic growth or redirect it away from the separator.…”
Section: Novel Current Collector Concept Materials and Chemistriesmentioning
confidence: 99%